Epitaxial Superconducting δ-MoN Films Grown by a Chemical Solution Method - Zhang, Yingying (2011)
The synthesis of pure δ-MoN with desired superconducting properties usually requires extreme conditions, such as high temperature and high pressure, which hinders its fundamental studies and applications. Herein, by using a chemical solution method, epitaxial δ-MoN thin films have been grown on c-cut Al2O3 substrates at a temperature lower than 900 °C and an ambient pressure. The films are phase pure and show a Tc of 13.0 K with a sharp transition. In addition, the films show a high critical field and excellent current carrying capabilities, which further prove the superior quality of these chemically prepared epitaxial thin films.